Performance optimization of an open simple-cycle gas turbine combined cooling, heating and power plant driven by basic oxygen furnace gas in China's steelmaking plants. (15th July 2020) - Chen, Lingen; Yang, Bo; Feng, Huijun; Ge, Yanlin; Xia, Shaojun
Abstract: Based on production data of some steelmaking plants in China and applying finite-time thermodynamics, this paper establishes a physical model of simple open gas turbine combined cooling, heating and power plant driven by basic oxygen furnace gas. Thermal process of each component is analyzed. Useful energy output rate and first law efficiency are considered as optimization objectives. Cases with or without constraints of fuel mass flow rate and overall size are investigated. In the case of without constraints, compressor inlet pressure drop (i.e. air mass flow rate) and pressure ratio are respectively optimized, and the maximum useful energy output rate is obtained. In the case of with constraints, it is found that the first law efficiency also exists maximum with respect to compressor inlet pressure drop and pressure ratio, the optimal flow area allocations among the components are obtained. The results show that maximum useful energy output rate and first law efficiency increase with heat source temperature, efficiencies of compressors and turbine, component flow area and cooling temperature, while decrease with heating temperature. Effects of energy and exergy saving, CO2 emission reduction and cost saving are analyzed compared with conventional separate generation plants, and partial model is validated. Highlights: A physical model of open gas turbine CCHP plant driven by BOFG is established. Useful energy output rate and first law efficiency are optimized by applying FTT. Compressor inlet pressure drop and pressure ratio are optimal variables. BOFG utilization model per hour could realize energy saving 0.45tce. CO2 emission reduction is 1.11tons per hour and cost saving is 1103 yuan per hour.